Searching for Information on the Internet: How Do Elementary School Students Use Search Engines on the Web - Drnovšek, Uroš (Revija za elementarno izobraževanje, 2009)
The Internet has become one of the most popular sources of finding diverse information, even among elementary school students. One of the primary goals of our research was to closely observe students' web searching strategies while they searched for knowledge about life science. We then analyzed different variables, such as the number of keywords students used when they were searching, time spent browsing different web pages, time spent selecting web pages, etc. We measured students' success in completing different web searching tasks and tried to find some factors that are important that led to this success. Students had the most success with the fact-finding task, while research-oriented and semi self-generated tasks proved to be much challenging. Most students were satisfied with the information they got within the first two search attempts and, on average, they browsed only three websites per task. Age was an important factor in determining students' overall success and time for browsing the web.